Leituras e usos do livro didático de História : relações professor-livro didático nos anos finais do ensino fundamental - Carvalho, Ana Beatriz dos Santos (2009)
This study is a research that has as object the relations beetwen textbooks and History teachers. The researched selected collection was: História: das Cavernas ao Terceiro Milênio, published by Editora Moderna, destined to the forthy last year of elementaty school. The general objective oh that research was to analyze the relationships between teachers and history textbooks in the final years (6th to 9th years) of elementary school, showing the ways and uses that are made of the textbooks by investigated teachers when teaching. The specific objectives were well defined: reviewing of the Brazilian history textbook, examining the history collection: História: das Cavernas ao Terceiro Milênio, adopted by MEC PNLD 2008, toward the final years of elementary school, focusing on the theoretical and methodological assumptions, the structure of the collection, the iconography and criteria usability, thinking about how teachers read, understand and use the textbook in the teaching and learning developed in the daily school and work for the production of a critical diagnosis of the historical knowledge conveyed by textbooks for history and methods of their use in the educational reality of the contemporary Brazilian society. The methodology combined document analysis, questionnaires and oral interviews with seven history teachers that uses the collectoin books in the years 2008 and 2009. The research enabled us to record and understand the view that teachers have these books, identifying strengths and weaknesses and explaining the meanings of these concepts that emerge. We conclude that greater knowledge about the concepts of users, in this case teachers, about the textbook that allows us to progress improvements that can provide important resource for education, allows us to identify indicators that demonstrate ways to read and use the books in the classroom, and highlights the need for changes that may be incorporated into the practice of teaching history.